# Thanks for the help with the sqrt problems

9,254 results

### Math Help please!!

Could someone show me how to solve these problems step by step.... I am confused on how to fully break this down to simpliest terms sqrt 3 * sqrt 15= sqrt 6 * sqrt 8 = sqrt 20 * sqrt 5 = since both terms are sqrt , you can combine them. sqrt 3* sqrt 15= sqrt (15*3)= sqrt 45 ...

### math,algebra,help

Directions are simplify by combining like terms. x radiacal 18 -3 radical 8x^2 can someone show me how to do these types of problems. thanks I cant determine the second term. For the first, I think you meant x sqrt(18) which reduces to x sqrt (9*3) or 3x sqrt 3 First remove ...

### Calculus

In these complex exponential problems, solve for x: 1)e^(i*pi) + 2e^(i*pi/4)=? 2)3+3=3i*sqrt(3)=xe^(i*pi/3) MY attempt: I'm not really sure of what they are asking. For the 1st one I used the e^ix=cos(x)+i*sin(x) and got -1+sqrt(2) +sqrt(2)i 2) I solved for x and fot (3+3i*...

### Mathematics

sqrt 6 * sqrt 8 also sqrt 7 * sqrt 5 6.92820323 and 5.916079783 So you can see the steps — sqrt 6 * sqrt 8 = sqrt 48 sqrt 7 * sqrt 5 = sqrt 35 I hope this helps a little more. Thanks for asking.

### Math(Roots)

sqrt(24) *I don't really get this stuff.Can somebody please help me? The square root of 24 is 4.898979485566356 I know that..lol,but it says not to use decimals.Here is an example they gave me. Ex.sqrt(18)=sqrt(2*3*3)=3sqrt(2) sqrt[24] = sqrt[4*2*3] = sqrt[4]*sqrt[2]*sqrt[3]= ...

### Algebra

Evaluate sqrt7x (sqrt x-7 sqrt7) Show your work. sqrt(7)*sqrt(x)-sqrt(7)*7*sqrt(7) sqrt(7*x)-7*sqrt(7*7) sqrt(7x)-7*sqrt(7^2) x*sqrt 7x-49*x ^^^ would this be my final answer?

### Math

How do you find a square root of a number that's not a perfect square? I'm very confused. The book doesn't explain it too well. You can approximate it or simplify it in terms of (products of) square roots of smaller numbers. E.g. consider sqrt[117] The number 177 can be ...

### Inequality

When I solve the inquality 2x^2 - 6 < 0, I get x < + or - sqrt(3) So how do I write the solution? Is it (+sqrt(3),-sqrt(3)) or (-infinity, sqrt(3))? Why? Thanks. So would this work? abs x < ( sqrt 3 ) or - sqrt 3<x<sqrt 3 The answer is given (+sqrt(3),-sqrt(3)) ...

### MATH

Can someone help me solve these problems? Thank you. [SQRT(2x2 + 5x + 6)]=x . [SQRT(x + 3)] = 2[SQRT(x)]

### Calculus

Evaluate the integral by changing to spherical coordinates. The outer boundaries are from 0 to 1. The middle one goes from -sqrt(1-x^2) to sqrt(1-x^2) The inner one goes from -sqrt(1-x^2-z^) to sqrt(1-x^2-z^) for 1/sqrt(x^2+y^2+z^2) dydzdx I don't understand how to get the ...

### Calculus

Evaluate the integral by changing to spherical coordinates. The outer boundaries are from 0 to 1. The middle one goes from -sqrt(1-x^2) to sqrt(1-x^2) The inner one goes from -sqrt(1-x^2-z^) to sqrt(1-x^2-z^) for 1/sqrt(x^2+y^2+z^2) dydzdx I don't understand how to get the ...

### Calculus

Evaluate the integral by changing to spherical coordinates. The outer boundaries are from 0 to 1. The middle one goes from -sqrt(1-x^2) to sqrt(1-x^2) The inner one goes from -sqrt(1-x^2-z^) to sqrt(1-x^2-z^) for 1/sqrt(x^2+y^2+z^2) dydzdx I don't understand how to get the ...

### Calculus

Evaluate the integral by changing to spherical coordinates. The outer boundaries are from 0 to 1. The middle one goes from -sqrt(1-x^2) to sqrt(1-x^2) The inner one goes from -sqrt(1-x^2-z^) to sqrt(1-x^2-z^) for 1/sqrt(x^2+y^2+z^2) dydzdx I don't understand how to get the ...

### math calculus please help!

l = lim as x approaches 0 of x/(the square root of (1+x) - the square root of (1-x) decide whether: l=-1 or l=0 or l=1 Let me make sure I understand the question. Do we have lim x->0 x/[sqrt(1+x) - sqrt(1-x)] ? If so then multiply the expression by [sqrt(1+x) + sqrt(1-x)]/[...

### Math/Calculus

Solve the initial-value problem. Am I using the wrong value for beta here, 2sqrt(2) or am I making a mistake somewhere else? Thanks. y''+4y'+6y=0, y(0)=2, y'(0)=4 r^2+4r+6=0, r=(-4 +/- sqrt(16-4(1)(6))/2 r=-2 +/- sqrt(2)*i , alpha = -2, beta = 2(sqrt(2)) y=e^-2x*(c1*cos(sqrt(2...

### Calculus

Please look at my work below: Solve the initial-value problem. y'' + 4y' + 6y = 0 , y(0) = 2 , y'(0) = 4 r^2+4r+6=0, r=(16 +/- Sqrt(4^2-4(1)(6)))/2(1) r=(16 +/- Sqrt(-8)) r=8 +/- Sqrt(2)*i, alpha=8, Beta=Sqrt(2) y(0)=2, e^(8*0)*(c1*cos(0)+c2*sin(0))=c2=2 y'(0)=4, c2=4 y(x)=e^(...

### Calculus

Evaluate the indefinite integral: 8x-x^2. I got this but I the homework system says its wrong:sqrt((-x-8)x)/(2*sqrt(x-8)*sqrt(x))*(((sqrt(x-8)*(x-4)*sqrt(x))-32*log(sqrt(x-8)+sqrt(x))

### algebra

am I right? 1. Simplify radical expression sqrt 50 5 sqrt ^2*** 2 sqrt ^5 5 sqrt ^10 5 2. Simplify the radical expression sqrt 56x^2 28x 2x sqrt 14*** 2x sqrt 7 sqrt 14x2 3. Simplify the radical expression. sqrt 490y^5w^6 2 sqrt 135y^2 2y sqrt 135*** 27 sqrt 15y^2 27y sqrt 15 ...

### Precalculs

I have no idea how to do these type of problems. -------Problem-------- Solve each equation on the interval 0 less than or equal to theta less than 2 pi 42. SQRT(3) sin theta + cos theta = 1 ---------------------- There is an example prior to the excersises that attempts to ...

### math help

15sqrt8x^15/5sqrt2x^4 remember that sqrt(a)/sqrt(b) = sqrt(a/b) simplify the inside. also notice that sqrt(x^11) = sqrt(x^10) * sqrt(x) = x^5 * sqrt(x)

### Calculus check

Given f(x)=x^4(2x^2-15). On what interval(s) is the graph of f concave upwards? A. (0, sqrt(3)) B. (-sqrt(3), 0) C. (-sqrt(3), 0) and (0, sqrt(3)) D. (-sqrt(3), sqrt(3)) E. (Negative infinity, -sqrt(3)) and (sqrt(3), infinity) I got E

### MATH

I need to simply this equation, but I got stuck. h/(4-sqrt(16+h)) = y First, I multiplied (4+sqrt(16+h)/(4+sqrt(16+h) to both sides, and I ended up with h(4+sqrt(16+h)/-h. Is this correct? (I tried to graph both equations to see if I would get the same graph, but I didn't, ...

### algebra

Simplify: 2 sqrt (3) + 6 sqrt(2) - 4 sqrt(3) + sqrt (2) a) 8 sqrt(2) - 3 sqrt(3) b) 6 sqrt(2) - 8 sqrt(3) c) 5 sqrt(6) d) 7 sqrt(2) - 2 sqrt(3) the answer i picked was d

### algebra

Simplify: sqrt (21) (sqrt(7) + sqrt(3)) a) 7 sqrt (3) + 3 sqrt(7) b) 7 sqrt(3) + sqrt (3) c) sqrt (210) d) sqrt (147) + sqrt (63)''. a

### linear algebra check

Use the Gram-Schmidt process to transform the basis [1 1 1] , [0 1 1] , [2 4 3] for the Euclidean space R3 into an orthonormal basis for R3. (Enter each vector in the form [x1, x2, ...]. Enter your answers as a comma-separated list.) so i went through the process and got [1/...

### algebra

simplify: square root of 5 + square root of 20 - square root of 27 + square root of 147. simplify: 6/4square root of 2 sqrt 5 + sqrt 20 - sqrt 27 + sqrt 147 = sqrt 5 + sqrt (4*5) - sqrt (3*9) + sqrt (49*3) = 3 sqrt 5 - 3 sqrt 3 + 7 sqrt 3 = 3 sqrt 5 + 4 sqrt 3 Your second ...

### Surds

Solve in the exact form. (sqrt of 4x+1)+(sqrt of x+1)=2 Someone showed me to do this next: Square both sides..so.. 4x+1+2((sqrt of 4x+1)•(sqrt of x+1))=4 I do not understand where the 2 come from ..and why do we need to multiply the sqrt of 4x+1 and sqrt of x+1 together to ...

### math

how would you simplify this equation: y = (x+3)/[(4-sqrt(16+h))] please help me! you have three variables. I am not certain "simplify" is an appropriate term here. ohhhh it was my mistake. I meant: y = h/[(4-sqrt(16+h))] y = h/[(4-sqrt(16+h))] rationalize the denominator.. y...

### algebra

simplify by combining like terms: x sqrt(18) - 3 sqrt(8x)sqrd If <sqrt(8x)sqrd> means [sqrt(8x)]^2, then that also equals 8x. So x sqrt(18) - 3 sqrt(8x)sqrd = x[sqrt(9*2)-3*8] = 3x(sqrt 2 -3

### Algebra

Multiplying sq rts sqrt18a^7b times sqrt27a^8b^6 Jake 1214- 18 = 9 * 2 then sqrt 18 = 3sqrt2 sqrt a^7 = a^3 * sqrt a 27 = 9 * 3 then sqrt 27 = 3 sqrt3 sqrt a^8 = a^4 sqrt b^6 = b^3 Now just multiply the like-terms together. 3sqrt6 and sqrt2a^4?

### 9th grade algebra (completing square)

Can you check the following? A1. (2x + 3)^2 = 25 sqrt(2x + 3)^2 = +-sqrt(25) 2x + 3 = +- 5 2x + 3 = 5, 2x + 3 = -5 2x = 2, 2x = -8 x = 1, x = -4 {-4, 1} A2. x^2 + 14x + 45 = 0 x^2 + 14x + __ = -45 + __ x^2 + 14x + 49 = -45 + 49 (x +7)^2 = 4 sqrt(x+7)^2 = +- sqrt(4) x + 7 = +- ...

### Math

So I am supposed to solve this without using a calculator: Sqrt[20]/10 - Sqrt[10]/Sqrt[32] - Sqrt[0.3125] + Sqrt[3 + 1/5] You can put this into WolframAlpha as is to make it prettier. Answer given is 1/2 * SQRT(5) I really don't know where to start here. I have 5 sqrt rules in...

### Math

Which is the exact value of the expression sqrt 32- sqrt 50 + sqrt 128 2 sqrt 7 7 sqrt 2 22 sqrt 2 2 sqrt 55

### Algebra

Which of these expressions is in simplified form? A. a ^3 sqrt 4 - b ^3 sqrt 2 / 2 B. sqrt 1/2x + sqrt 1/2z C. x^2 - 3x sqrt y / sqrt 3 D. sqrt 125x - x^2

### math,correction

simplify: sqrt ((7)/(100)) my work: 7 = 1sqrt (7) 100= 10 sqrt (1) (1)/(10) sqrt (7) my answer: (sqrt (7))/(10) Your answer is right but your statements: 7 = 1sqrt (7) 100= 10 sqrt (1) make no sense. how can sqrt(7)=7 ? you are saying 2.6457..=7 and 10sqrt(1) = 100 ---> 10 ...

### Algebra 2: Radicals URGENT!!

Could some kind, saintly soul help me solve this problem? Simplify: 8w sqrt(48w^5) - x^2 sqrt(3xw^2) . . =8w(√16)(√3)(√w^4)(√w) - x^2(√3)(√x)(√w^2) =32w^3(√3w) - wx^2(√3x) not much of a "simplification" really 8w sqrt(16*3w...

### Calculus - Second Order Differential Equations

Posted by COFFEE on Monday, July 9, 2007 at 9:10pm. download mp3 free instrumental remix Solve the initial-value problem. y'' + 4y' + 6y = 0 , y(0) = 2 , y'(0) = 4 r^2+4r+6=0, r=(16 +/- Sqrt(4^2-4(1)(6)))/2(1) r=(16 +/- Sqrt(-8)) r=8 +/- Sqrt(2)*i, alpha=8, Beta=Sqrt(2) y(0)=2...

### Algebra

1 last square root : Rationalize the denominator 5/sqrt[3]+sqrt[5]= 5*sqrt[3]-sqrt[5]/ sqrt[3]sqrt5[5]*sqrt[3]-sqrt[5]= 5sqrt[3]-5sqrt[5]/sqrt[9]-sqrt[15]+sqrt[15]- sqrt[25]= 5sqrt[3]-5sqrt[5]/-16 = 5sqrt[3]-5sqrt[5]/ -2

### math

solve 2x^2+3x+8=0 and express the solutions in a+bi form. Let's use the quadratic formula to solve for x and express those solutions in a+bi form. x = [-b + or - sqrt(b^2 - 4ac)]/2a Note: sqrt = square root. a = 2, b = 3, and c = 8 from your problem. Therefore: x = [-3 + or - ...

### Math

Find of g(f(x)) when f(x)=sqrt(x+3) and g(x)=(x^2+2)/x. a. g(f(x))=(x^2+2)(sqrt(x+3))/x b. g(f(x))=(x+5)/(sqrt(x+3)) c. g(f(x))=(x^2+6x+11)/(sqrt(x+3)) d. g(f(x))=(sqrt(((x^2+2)/x)+3) Every time I work this problem, I get some crazy answer. Can someone please help me?

### algebra

Simplify -11 sqrt 112. -44 sqrt 7******** -176 sqrt 7 -27 sqrt 7 4 sqrt 7 Is this right? and I need to show my work, idk the steps

### ap calculus

Which of the following definite integrals gives the length of y = e^(e^x) between x=0 and x=1? All the answers are preceded by the integral sign from 0 to 1. (a) sqrt[1 + e^(2*(x+e^x))] dx (b) sqrt[1 + e^(4x)] dx (c) sqrt[1 + e^(x+e^x)] dx (d) sqrt[1 + e^(2e^x)] dx (e) sqrt[e...

### Algebra

I have a question if someone could help, please explain it. Given b = -1 and h = -1, what is the equation of the graph if the parent function is y = sqrt (x) Answers: a.y = sqrt(x-1) b.y = sqrt (-x+1) c.y = - sqrt (-x-1) d.y = sqrt(-x-1) I think it is "b"

### algebra

simplify: sqrt (28) a) 4 sqrt (7) b) 7 sqrt (2) c) 2 sqrt (7) d) sqrt (7) c im just making show that they are correct sorry for posting up so many

### Algebra 1

sqrt r - sqrt s/ sqrt r + sqrt s =r sqrt r- sqrt rs +sqrt s/ r can someone check this for me please.

### Calculus

show lim x->3 (sqrt(x)) = (sqrt(c)) hint: 0< |sqrt(x)-sqrt(c)|= (|x-c|)/(sqrt(x)+sqrt(c))<(1/(sqrt(c))*|x-c|

### Calculus

show lim x->3 (sqrt(x)) = (sqrt(c)) hint: 0< |sqrt(x)-sqrt(c)|= (|x-c|)/(sqrt(x)+sqrt(c))<(1/(sqrt(c))*|x-c|

### Calculus(Derivative of ln)

I get everything, but I can't seem to crack this one out, only one I got problems on.. -sqrt[x^2 +1]/x + ln(x + sqrt[x^2 + 1])

### algebra,math,help

Use Property 2 to simplify each of the following radical expressions. sqrt (10)/ sqrt(49) My answer: sqrt (10) / (7) THis next one i need help: Use the properties for radicals to simplify each of the following expressions. Assume that all variables represent positive real ...

### algebra

Simplify: ( sqrt (2) + sqrt (3) ) ( sqrt (2) - sqrt (3) )? a) 2 - 2 sqrt (6) - 3 b) -1 c) 2 + 2 sqrt (6) - 3 d) 5 i just need to know if my answer or right or wrong. i think the answer is b thanks

### Real Analysis (Math)

Prove: [1/sqrt(2)] [sqrt(a) + sqrt(b)] <= sqrt(a + b) <= sqrt(a) + sqrt(b) for all non-negative real numbers a and b.

### Math

How would I do: sqrt32a^8b + sqrt50a^16b Are the exponents 8b and 16b or 8 and 16? I'll assume they are 8a and 16a sqrt 32 = sqrt (16*2) = 4 sqrt 2 sqrt 50 = sqrt (25*2) = 5 sqrt 2 sqrt32 a^(3b) + sqrt50a^(2b) = sqrt2*a^(8b)[4 + 5(a^8b)] There are many ways to write it, but ...

### Algebra 2

Simplify the number using the imaginary unit i. (sqrt)of -28 •2(sqrt)-7 •-2 (sqrt)-7 •i (sqrt)28 •2i (sqrt)7

### some algebra help (radicals)

I hope I am writing this down right.. I am trying to do some practice questions to learn 10^5 (sqrt)2y - 4^5 (sqrt)2y I am trying to figure out how to solve this They gave us some answers to choose from, but I am clueless on how to solve this 6y ^5 (sqrt)2 6y ^5 (sqrt)2y - 6y...

### math

d/dx x(1+y)^(1/2) + y(1+x)^(1/2)=0. Can some1 show me the calculation because i didn't get like the answer. [ans=-1/(1+x)^2 but my calculation=-(sqrt(y+1) (2 sqrt(x+1) sqrt(y+1)+y)/(sqrt(x+1) (2 sqrt(x+1) sqrt(y+1)+x)]

### math

d/dx x(1+y)^(1/2) + y(1+x)^(1/2)=0. Can some1 show me the calculation because i didn't get like the answer. [ans=-1/(1+x)^2 but my calculation=-(sqrt(y+1) (2 sqrt(x+1) sqrt(y+1)+y)/(sqrt(x+1) (2 sqrt(x+1) sqrt(y+1)+x)]

### math

Hi, I was working on my math homework and I was stumbling on these problems. I tried looking at the solutions but my answers were completely off. Here are the ones I'm stuck on: If vectors O(0,0,0), A(6,0,0), B(6,-sqrt(24), sqrt(12)), and C(0,-sqrt(24), sqrt(12)) form a square...

### Calculus

Graph the curve and find its exact length. x = e^t + e^-t, y = 5 - 2t, from 0 to 3 Length = Integral from 0 to 3 of: Sqrt[(dx/dt)^2 + (dy/dt)^2] dx/dt = e^t - e^-t, correct? dy/dt = -t^2 - 5t, correct? So: Integral from 0 to 3 of Sqrt[(e^t - e^-t)^2 + (-t^2 - 5t)^2] Then what ...

### Calculus - Second Order Differential Equations

Solve the initial-value problem. y'' + 4y' + 6y = 0 , y(0) = 2 , y'(0) = 4 r^2+4r+6=0, r=(16 +/- Sqrt(4^2-4(1)(6)))/2(1) r=(16 +/- Sqrt(-8)) r=8 +/- Sqrt(2)*i, alpha=8, Beta=Sqrt(2) y(0)=2, e^(8*0)*(c1*cos(0)+c2*sin(0))=c2=2 y'(0)=4, c2=4 y(x)=e^(8x)*(2*cos(Sqrt(2)x)+4*sin(...

### Algebra 2

Operations with Complex Numbers Simplify. 1. sqrt(-144) 2. sqrt(-64x^4) 3. sqrt(-13)*sqrt(-26) 4. (-2i)(-6i)(4i) 5. i13 6. i38 7. (5 – 2i) + (4 + 4i) 8. (3 – 4i) – (1 – 4i) 9. (3 + 4i)(3 – 4i) 10. (6 – 2i)(1 + i) 11. (4i)/(3+i) 12. (10+i)/(4-i) 13. (-5 + 2i)(6 – ...

### math

determine the area of triangle abc when side ab= square root of x, side bc= square root of x, and side ca= the square root of the square root of x. So how do I solve it. How do I add the square root of x + the square root of x + the square root of the square root of x? what is...

### Calculus - Integrating

Question: ∫(x^2)/sqrt(x^2+1) u=x^2+1 , x^2= u-1, du=2xdx ∫(u-1)/sqrt(u) , expand ∫u/sqrt(u) - 1/sqrt(u) Integrate: 2/3(u^(3/2)) - 2u^(1/2) + c My answer: [ 2/3(x^2+1)^(3/2) - 2(x^2+1) + c ] When I took the derivative of this to check my answer, it was not (x^2)/sqrt(x^2+...

### Algebra

Need to get these problems checked-- 31. Determine whether the sequence 7, 21, 35, 49 is geometric. If so, find its common ratio. a. no b. yes, common ratio of 14 c. yes, common ratio of 12 I'm stuck between A and B.. 32. What are the next three terms of the geometric sequence...

### Math

For f(x) = 2sinx + (sinx)^3 + tanx find f'(pi/3). Ok, so what I tried was... f'(x) = 2cosx + cosx(3(sinx)^2) + (sinx/cosx) pi/3 = (1/2, sqrt(3)/2) therefore, 2(1/2) + 1/2(3(sqrt(3)/2)(sqrt(3)/2) + (sqrt(3)/2 (2/1)) 1 + .5(3 (3/4)) + sqrt(3) 1 + .5(9/4) + sqrt(3) = 4.982... but...

### MATH

cos(x)=2 and sin(x)=5 Thanks for your previous answers mathmate. No. It's not a typo. I was wondering if someone could explain to me when in real life would I need to solve such problems, or similar, besides answering problems from a textbook. When ever I ask this question I ...

### radical equation

2^x+20=15+3^x A)1 B)16 C)-5 D)25 I chose c but i got it wrong i am having a problem understanding it. Let me rewrite the question in a more standard format. 2* sqrt(x)+20=15 + 3*sqrt(x) where * means multiply, and sqrt means the square root. Your use of ^ for square root is ...

### Algebra

SIMPLIFY: ROOT 0F 7 * ROOT OF 14 SIMPLIFY: ROOT OF 1/5 EVALUATE, IF POSSIBLE: ROOT OF 9/16 (I GOT 3/4 BUT I WAS NOT SURE IF THAT WAS CORRECT OR NOT) SIMPLIFY. ASSUME X REPRESENTS A POSITIVE NUMBER: ROOT OF 45X^4 ROOT 0F 7 * ROOT OF 14 = sqrt 7 * sqrt 7 * sqrt 2 = 7 sqrt 2 ROOT...

### Algebra

Solve for s: h=(square root of 3)times s/2 and solve for h V= (pi)r squared h / 3 Solve for s: h=(square root of 3)times s/2 Multiply both sides by 2. 2h = (sqrt 3)*s*2/2 which cancels the 2 on the right. 2h = (sqrt 3)*s Now divide the right side by everything except what you ...

### calculus

prove that d/dx 4x .√(x + √x) = 6x+5 (x)1/2/√(x + √x) solution is d/dx 4x.[x+(x)1/2]1/2 = d/dx 4x.[x+(x)^1/2]^1/2 d/dx 4x.[x+(x)^1/2]^1/2 Product Rule = 4x[1/2(x+(x)^1/2)^-1/2 * (1+1/2x^-1/2) +[x+(x)^1/2]^1/2*4 d/dx(4 x sqrt(x+sqrt(x))) = (2 (1/(2 sqrt(...

### math,correction

the problem reads: evaluate sqrt (-4) if possible. my answer: sqrt (-4)<0 therefore this is not a real number looks correct you cannot take the square root of a negative number in the real number set. Have you learned the imaginary number i = sqrt(-1) ?? if so you can do: ...

### math

Can someone please help me with the following problems Determine if the triple numbers are can be sides of a right triangle? sqrt(10)sqrt(13)sqrt(23) The length of thy hypotenuse of a right triangle equals the length of one of legs of the triangle A) always true B) sometimes ...

### Algebra 1

sqrt r - sqrt s/ sqrt r + sqrt s =r sqrt r- sqrt rs +sqrt s/ r Can see if I did this right.

### Algebra-drwls please check!

Posted by Megan on Tuesday, October 12, 2010 at 3:44pm. I have a question if someone could help, please explain it. Given b = -1 and h = -1, what is the equation of the graph if the parent function is y = sqrt (x) Answers: a.y = sqrt(x-1) b.y = sqrt (-x+1) c.y = - sqrt (-x-1) ...

### Math

f(x)= 4-x^2 and g(x)= sqrt (x) find the implied domain of fg(x) fg(x)= f(sqrt(x)) fg(x)= 4-(sqrt(x))^2 fg(x)=4-(sqrt x)(sqrt x) fg(x)=4-x domain= (x:x=all real numbers) Am I correct?

### algebra

sqrt(45)+ sqrt(20)+ sqrt(5)-sqrt(125)=?? I came up with 6sqrt5 I know it's wrong. I think I messed up the breakdown of the sqrt of 125

### linear algebra urgent

For the orthogonal matrix A = 1/sqrt(2) -1/sqrt(2) -1/(sqrt(2)) -1/sqrt(2) verify that (Ax,Ay)=(x,y) for any vectors x and y in R2. Can someone please explain this

### rationalizing

sqrt(18) - sqrt(17) How does this expression equal 1/(sqrt(18) + sqrt(17)) ? How would you change it like that? And why is this good to use when not using a calculator?

### math,correction

i am really trying is this correct. solve: 5(x-2)^2 = 3 MY ANSWER THAT I GOT IS: X = 2 +- (SQRT (3) )/(5) no. 5(x-2)^2 = 3 (x-2)^2 = 3/5 x-2 = +- sqrt (3/5) x= 2 +- sqrt (3/5) so the whole fraction of 3/5 is inside the sqrt yes

### Calculus (please check my answer)

Find the Avrage value of the function i=15(1-e to the power of -1/2 t) from t=0 and t=4? A.7.5 sqrt 1+4e^-2 -e^-4 <<<<not sure though B.7.5 sqrt 4-2e^-2 + e^-4 C.7.5 sqrt 4+4e^-2 - e^-4 D.7.5 sqrt 5-2e^-2 + e^-4

### algebra

Rationalize the denominator, assume that all expressions under radicals represent postive numbers. sqrt:a - sqrt:b/sqrt:a + sqrt:b

### Math

Simplify the product. -9 sqrt 28a^2 * 1/3 sqrt 63a I came until -3 sqrt 49a^2 * sqrt 36a, but then I got confused...

### math-Inverse functions

f(x)=-4x-2 & g(x)=5x-6. Find (f*g) and state domain. f(x)-x^2-1 what is the equation for f^-1(x)? f(x)=3x+2, find f(f^-1(14)). f(x)=4x+7 and g(x)=3x-5 find (f*g)(-4) f(x)=sqrt x+3 what is equation for f^-1(x)? Graph y=sqrt x-2 +5 which point lies on graph? A(7,6) B(0,5) C(-2,5...

### algebra

can someone tell me if i did the problem correct (solve by completing the square) 4x^2+2x-3=0 x^2+(1/2)=3/4 x^2+(1/2)+(1/4)^2=3/4+(1/4)^2 (x+1/4)^2=13/16 x+1/4=+-sqrt 13/16 x+1/4=+-sqrt 13/4 x=-1/4+-sqrt 13/4 x=-1+-sqrt 13/4

### Math

1. The length of the hypotenuse of a 30-60-90 triangle is 7. Find the perimeter. A) 7/2+21/2 sqrt 3 B) 21+7 sqrt 3 C) 7+21 sqrt 3 D) 21/2 + 7/2 sqrt 3 Could someone please help me, I don't know how to do this. Thank you!

### Algebra 1

Combine the following into a single expression of the form a x sqrt b. Sqrt 6 + Sqrt 54 + Sqrt 150

### algebra

I asked a question and it was answered by Steve. He had the numbers wrong. The problem should be sqrt of 18 over (sqrt of 8)-3. not sqrt of 18 -3. I got 2+sqrt of 8. Is it correct?

### Math/Calculus #2

Integrate: 1/(x-sqrt(x+2) dx I came up with: (2/3)(2*ln((sqrt(x+2))-2)+ln((sqrt(x+2))-1)) but it keeps coming back the wrong answer even though I integrated correctly. Is there a way to simplify this answer, and if so, how? I found: Ln[x-sqrt(x+2)] + 1/3Ln[(sqrt(x+2)-2)/(sqrt(...

### algebra

simplify: sqrt (121/9) a) 11/3 b) sqrt (11/3) c) sqrt(11 / sqrt 3) d)3 sqrt (11) a is the answer

### pre-cal

Find the roots of the function f(x)= x^2+2x+2 Determine f(x) a) (x+1-i)(x+1+i) b)(x+1-i sqrt of 2)(x+1+i sqrt of 2) c)x-1+i)(x-1-i) d)x-1+i sqrt of 2) (x-1-i sqrt of 2) Please Help! For all of these, use the rule [f(x) + ai]*[(f(x) - ai} = [f(x)]^2 + a^2 where a is a real ...

### Pre-Cal(Please check)

1)f(x) = -x + sqrt 4 - x^2 Find f(-2) -(-2) + sqrt 4 - (-2)^2 = 2 + sqrt 4 + 4 2 + sqrt 8 = 4.828 Is this correct?

### algebra

simplify the following radical expression: 3 sqrt () -216x^2/x^2 a) sqrt() -6x b)-6 c)-6 sqrt()x d) 6 sqrt()-x

### algebra

Simplify: sqrt (12) - sqrt (27) a) - sqrt (15) b) -5 sqrt (3) c) -15 sqrt (3) d) -sqrt (3) i think d

### Calculus

so we are doing integrals and I have this question on my assignment and I can't seem to get it, because we have the trig substituion rules, but the number isn't even so its not a perfect square and I just cant get it, so any help would be greatly appreciated. The question is...

### calc - limits

I have been trying to figure out these limit problems and I get stuck on trying to move the function around to make it possible to solve. The first one is: lim sinx - cosx / tanx - 1 x--> (pi/4) All I've gotten so far is to replace tanx with sinx/cosx but I don't even know ...

### algebra

1.what is the simplest form of the producy sqrt 50x^7y^7 * sqrt 6 xy^4 2. What is the simplest form of the radical expression 4^3 sqrt 3x + 5^3 sqrt 10x 3. What is the simplest form of the radical expression sqrt 2 + sqrt5 / sqrt 2 - sqrt 5 if someone could explain the steps ...

### Calculus

Could someone please explain this to me? Differentiate. h(u)= 10^(sqrt(u)) h'(u)= 10^(sqrt(u))*log(10)(d/du(sqrt(u))) h'(u)= 10^(sqrt(u))*((1)/(2*sqrt(u)))*log(10)

### exprxion

. Simplify the following expressions points) a. sqrt(20) + sqrt(5) b. (6 + sqrt(18))/6 c. sqrt(9y^4x^0.5)^0.5

### Calculus

derivative of ((Sqrt(x+3y)+sqrt(3xy))=(sqrt(21)+sqrt(90)) at point (6,5)google

### Calculus

Find the RMS value of the function i=15[1-e^(-1/2t)] from t=0 to t=4 A. 7.5[sqrt(1+4e^-2 -e^-4)] B. 7.5[sqrt(4-2e^-2 +e^-4)] C. 7.5[sqrt(4+4e^-2 -e^-4)] D. 7.5[sqrt(5-2e^-2 +e^-4)]